PENAGGULANGAN TINDAK PIDANA PENIPUAN MELALUI TRANSFER MOBILE MBANKING - Zainudin Hasan; Anisa Merti Ayu, Chinthia Dita M, Mayse Trisnawati, M. Ardan Aldika R.A (ADISAM PUBLISHER, 2024)
As time goes by, technological developments have increased very rapidly. The development of this technology has penetrated all aspects of human life, from information and communication to the financial sector. In the financial world, especially banking, utilizes advances in technology to make it easier for customers to carry out financial transactions by shortening, simplifying and speeding up transactions. Through the development of this technology, it makes it easier for social interaction between one another, but behind that, all people must continue to anticipate to maintain the security of their important data in order to avoid unwanted things and one of them is their banking data which is often targeted. Criminals in the internet world are rampant because of the carelessness and ignorance of banking account holders. Crime in cyberspace or cyber (cyber crime) is a form of crime related to the world of technology and has been regulated in laws and regulations relating to technology and national information which contain elements of criminal acts committed in cyberspace which are considered to be detrimental to people. others, organizations or other parties who feel they have been harmed by crime in cyberspace.